2022
DOI: 10.3390/biom12101390
|View full text |Cite
|
Sign up to set email alerts
|

Use of Visual Electrophysiology to Monitor Retinal and Optic Nerve Toxicity

Abstract: It is important for clinicians to consider exposure to toxic substances and nutritional deficiencies when diagnosing and managing cases of vision loss. In these cases, physiologic damage can alter the function of key components of the visual pathway before morphologic changes can be detected by traditional imaging methods. Electrophysiologic tests can aid in the early detection of such functional changes to visual pathway components, including the retina or optic nerve. This review provides an overview of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 116 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…The cause of retinal ischemia induced by cisplatin/carboplatin is uncertain, but various mechanisms have been proposed. Excessive oxidative stress is believed to be the cause of retinal toxicity [ 15 ]. In vitro studies have indicated a link between cisplatin-induced platelet activation and the activation of phospholipase A2, which may explain the thrombotic side effects of cisplatin [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of retinal ischemia induced by cisplatin/carboplatin is uncertain, but various mechanisms have been proposed. Excessive oxidative stress is believed to be the cause of retinal toxicity [ 15 ]. In vitro studies have indicated a link between cisplatin-induced platelet activation and the activation of phospholipase A2, which may explain the thrombotic side effects of cisplatin [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used the ffERG recording at the start of vigabatrin treatment for each patient as its own reference and the expectation was improved responses while growing up. The most stable variable to compare is the 30 Hz flicker response (Chiang et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To ensure consistency in recording ERG tests, the International Society for Clinical Electrophysiology of Vision (ISCEV) has established standards [11]. This facilitates crosslaboratory comparisons and is crucial for research on retinal diseases and accurate patient monitoring over time.…”
Section: Principles Of Erg Recording and Methodological Detailsmentioning
confidence: 99%
“…It is important to note that electronegative ERG patterns are not exclusive to IRDs [10]. They may also manifest in acquired conditions that impact one or both eyes, including but not limited to siderosis, drug toxicity, central retinal artery occlusion (CRAO), central retinal artery occlusion (CRVO), paraneoplastic or autoimmune retinopathies, and vitamin A deficiency [11][12][13]. It is helpful to gather information about a disease's onset time, progression course, and family history to better understand and differentiate between inherited and acquired diseases.…”
Section: Electronegative Erg: Pathophysiology and Associated Diseasesmentioning
confidence: 99%